(untitled) (Research, Society and Development, 2021)
Introduction: The senescence process leads to a decline in cognitive functional capacity and adaptive responses that are necessary to perform activities of daily living, leading to a higher risk of morbidity and mortality. Studies show that aging can be associated with social isolation, which leads to several damages to physical and mental health. In December 2019, the first case of the new coronavirus was registered and, to contain the transmission, sanitary measures were taken, including social isolation. Objective: To investigate the effects of social isolation on physical and mental health in elderly community members during the COVID-19 pandemic. Methods: This is an integrative review study, carried out systematically based on the guiding question “What are the effects of the social isolation of the COVID-19 pandemic for physical and mental health in elderly people?”.Results: The studies prioritized the effects on the mental health of the elderly population, with the need to expand the investigation for the physical health of the elderly population, in the context of social isolation.